Use patterns of the Philippine Information Agency Library users with implications for the improvement of information resources and services - Viray, Barbara Anne G. (Institute of Library Science, University of the Philippines Diliman, 1993)
This study is about the Use-Patterns of the Philippine Information Agency library users: with Implications for the Improvement of its Information Resources and Services. It seeks to find out how the users evaluate the library resources and service with the identification of its most useful resource material and service. It also aims to discover the users' purpose in needing information, searching method and information seeking behavior.